In Vivo Cannulation Methods for Cardiomyocytes Isolation from Heart Disease Models - Jian, Zhong (PLoS One, 2016)
Isolation of high quality cardiomyocytes is critically important for achieving successful experiments in many cellular and molecular cardiology studies. Methods for isolating cardiomyocytes from the murine heart generally are time-sensitive and experience-dependent, and often fail to produce high quality cells. Major technical difficulties can be related to the surgical procedures needed to explant the heart and to cannulate the vessel to mount onto the Langendorff system before in vitro reperfusion can begin. During this period, transient hypoxia and ischemia may damage the heart, resulting in low yield and poor quality of cells, especially for heart disease models that have fragile cells. We have developed novel in vivo cannulation methods to minimize hypoxia and ischemia, and fine-tuned the entire protocol to produce high quality ventricular myocytes. The high cell quality has been confirmed using important structural and functional criteria such as morphology, t-tubule structure, action potential morphology, Ca(2+) signaling, responsiveness to beta-adrenergic agonist, and ability to have robust contraction under mechanically loaded condition. Together these assessments show the preservation of the cardiac excitation–contraction machinery in cells isolated using this technique. The in vivo cannulation method enables consistent isolation of high-quality cardiomyocytes, even from heart disease models that were notoriously difficult for cell isolation using traditional methods.